Porphyromonas gingivalis Promotes 4-Nitroquinoline-1-Oxide-Induced Oral Carcinogenesis With an Alteration of Fatty Acid Metabolism - Wu, Jia-shun; Zheng, Min; Zhang, Mei; Pang, Xin; Li, Li; Wang, Sha-sha; Yang, Xiao; Wu, Jing-biao; Tang, Ya-jie; Tang, Ya-ling; Liang, Xin-hua (Frontiers in Microbiology, 2018)
Microbiota has been widely considered to play a critical role in human carcinogenesis. Human papilloma virus, hepatitis B and C virus and helicobacter pylori are implicated in the pathogenesis of cancer of uterine cervix, liver and stomach, respectively. However, whether Porphyromonas gingivalis (P. gingivalis), a common gram negative oral bacteria, is associated with oral carcinogenesis still remains unclear and its underlying mechanism needs to be addressed. Here, we established a combined experimental system of 4NQO-induced oral carcinoma model and chronic periodontitis model and investigated the effects of P. gingivalis infection on oral carcinogenesis and fatty acid metabolism during oral carcinogenesis. The data showed that in this animal model, P. gingivalis infection induced mice periodontitis, increased the tongue lesion size and multiplicity of each mouse and promoted oral cancer development. P. gingivalis treatment significantly increased the level of free fatty acids and altered the fatty acid profile in tongue tissues and the serum of mice. And P. gingivalis induced the formation of fatty liver of the mice. Besides, immunohistochemical analysis and qRT-PCR showed that the expression of fatty-acid synthase (FASN) and acetyl-CoA carboxylase 1 (ACC1) were increased in the tongue and liver tissues of 4NQO-treated mice infected with P. gingivalis. These results showed that P. gingivalis promoted oral carcinogenesis and aggravated disturbance of fatty acid metabolism, indicating a close association among P. gingivalis, lipid metabolic and oral carcinogenesis.